Potentially toxic freshwater fish varieties - Putri, Amelia Pardiana; Bilqis, Jihan; Zikra, Amalia; Surtikanti, Hertien Koosbandiah (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Polluted waters generally contain materials harmful to human health, factory waste, metal waste, community waste can pollute these waters. Although polluted, there are some organisms that are able to survive in such conditions, such as catfish. The purpose of this article is to determine the diversity in aquatic ecosystems polluted by textile waste through bioindicators in the form of fish. The result of this study was the discovery of 3 species of fish that are able to adapt to polluted waters, namely Clarias batrachus, Pterygoplichthys pardalis, and Fundulus Grandis. The method used is in the form of a literature study on topics relevant to the purpose of this article. The results show that polluted water conditions can affect diversity in aquatic ecosystems, evidenced by the development of invasive species and the reduction of native species in a freshwater ecosystem. Species that are able to survive in polluted water conditions may contain harmful substances such as heavy metals and should not be consumed by humans.